Vitamin D deficiency and benign paroxysmal positioning vertigo. (3rd April 2019) - Carneiro de Sousa, Pedro Jorge Matos; Abreu Pereira, Diogo Manuel; Carneiro Melo Pereira de Magalhães, Pedro; Duarte, Delfim Rui da Silva; Trigueiros da Silva Cunha, Nuno Maria
Abstract: Objectives: Benign paroxysmal positioning vertigo (BPPV) has significant recurrence rates, mainly in older patients. The etiopathology of recurrent BPPV is possibly related to low serum vitamin D levels. Finding a therapeutic weapon will help with these complicated cases, reducing disability, falling risk and also health care costs. Study design: Clinical trial : one-year duration. Setting: Ten patients with diagnosis of BPPV made by history and physical examination and at least two episodes of documented BPPV in the previous two years and chronic complaints of dizziness. Neurologic and other otological diseases were excluded for these patients. Subjects and methods: Vitamin D was evaluated by measuring serum 25-hydroxyvitamin D (25-OHD). Levels below 20 ng/mL were considered deficiency and levels between 20 and 30 ng/mL were considered insufficiency. Half of the patients (treatment group) started a treatment with cholecalciferol while the remaining patients were the control group. All of the patients were reevaluated every three months. Results: All patients of the treatment group did not have any subsequent episode of positional vertigo, dizziness complaints or nystagmus evoked by provocative manoeuvers. At reevaluations, the mean value of serum 25-OHD for the treatment group had increased noticeably. It was also significantly higher than the mean value of control group. All patients of control group had positional vertigo episodes, as well as positional nystagmus at office reevaluations. Conclusion: These results support the need to systematically measure and correct vitamin D levels in patients with recurrent BPPV.